2020
DOI: 10.1097/crd.0000000000000363
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin as a Therapeutic Target in Heart Failure

Abstract: Heart failure is a major source of morbidity and mortality, driven, in part, by maladaptive sympathetic hyperactivity in response to poor cardiac output. Current therapies target β-adrenergic and angiotensin II G proteincoupled receptors to reduce adverse cardiac remodeling and improve clinical outcomes; however, there is a pressing need for new therapeutic approaches to preserve cardiac function. β-arrestin is a multifunctional protein which has come under analysis in recent years as a key player in G protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 79 publications
2
4
0
Order By: Relevance
“…In addition, the mRNA level of ARRB2 with rs75428611-G was also higher than A allele using human lymphocytes. Our results demonstrated the fact that ARRB2 expression level was positively correlated to prognosis of HF patients, which favors the protective role of ARRB2 in HF and is in line with previous reports [23, 24].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, the mRNA level of ARRB2 with rs75428611-G was also higher than A allele using human lymphocytes. Our results demonstrated the fact that ARRB2 expression level was positively correlated to prognosis of HF patients, which favors the protective role of ARRB2 in HF and is in line with previous reports [23, 24].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the mRNA level of ARRB2 with rs75428611-G was also higher than A allele using human lymphocytes. Our results demonstrated the fact that ARRB2 expression level was positively correlated to prognosis of HF patients, which favors the protective role of ARRB2 in HF and is in line with previous reports [23,24]. However, recent study conducted by Wang et al [7] has found that ARRB2 could mediate cardiac ischemiareperfusion injury by inhibiting GPCR-independent cell survival signaling.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Biased signaling occurs when different ligands, upon interaction with a given receptor, trigger distinct signaling pathways and responses . Biased ligands for AT 1 Rs are well documented, with several prototypical analogues biased toward G protein activation or β-arrestin (βarr) recruitment. For instance, TRV027 induces βarr recruitment (equivalent in magnitude to that observed for Ang II) while antagonizing Ang II-mediated G protein-dependent signaling. , Prosurvival effects of TRV027 and other βarr-biased AT 1 R ligands linked to the βarr-mediated signaling and antagonism of G protein-mediated vasoconstriction and maladaptive phenotypes were suggested to be beneficial in treating myocardial fibrosis and cardiac hypertrophy. …”
Section: Introductionmentioning
confidence: 99%
“…Heart failure (HF) is a multifaceted clinical syndrome characterized by significant morbidity and mortality. 1 The diagnostic criteria for HF include objective evidence of pulmonary or systemic congestion, as well as elevated levels of natriuretic peptides. In recent years, the incidence and prevalence of HF have increased continuously due to the growing aging population and presence of HF-related risk factors, such as hypertension, obesity, and diabetes.…”
Section: Introductionmentioning
confidence: 99%